Inductive Coupled In-Circuit Impedance Monitoring of Electrical System Using Two-Port ABCD Network Approach - Li, Kang Rong (2016)
By treating the inductive coupling probes and the electrical system to be monitored as three cascaded two-port ABCD networks, the in-circuit impedance of the electrical system can be extracted with ease. The proposed method simplifies the setup calibration and allows real-time impedance monitoring of critical electrical system to be implemented without interrupting its normal operating conditions. In this paper, the theory behind the proposed ABCD networks approach is described. The proposed approach has overcome the poor measurement accuracy of the conventional inductive coupling calibration method above 30 MHz and has achieved good accuracy up to 100 MHz with a maximum measurement deviation of 3.6%. Finally, using a dc-powered motor as a practical example, the ability to detect the change of in-circuit impedance of the motor under different operating conditions is demonstrated.